Peran Katekis dalam Mendidik Remaja Paroki St. Maria Mangdalena Nangahure tentang Bahaya Minuman Keras - Veronika Nato Kolin; Intansakti Pius X (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research aims to determine the role of catechists in educating the youth of St. Maria Magdalena Nangahure about the dangers of alcohol. Liquor is a drink that contains alcohol, if consumed excessively and continuously it will be detrimental and dangerous both physically and mentally, thus affecting human behavior and thinking. Other consequences will have an impact on his social life, both with his family and his relationship with the surrounding community. The research subjects were teenagers from St. Maria Mangdalena Nangahure about the dangers of drinking alcohol. The qualitative method is a method that focuses on in-depth observation. Therefore, the use of qualitative methods in research can create a more comprehensive study of a phenomenon. Qualitative research that focuses on humanism or individual and human behavior is a response to the awareness that all consequences of human actions are influenced by internal aspects of the individual.